2014
DOI: 10.1007/s11356-014-3824-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of caffeic acid against hypothalamic neuropeptides alterations induced by malathion in rat

Abstract: Exposure to pesticides is suspected to cause human health problems. Our study aimed to evaluate preventive effects of caffeic acid (3,4-dihydroxycinnamic acid) in the hypothalamus against malathion-induced neuropeptides gene expression alterations. Malathion at 100 mg/kg was administered intragastrically to rats alone or in combination with caffeic acid at 100 mg/kg during 4 weeks. A molecular expression of hypothalamic neuropeptides and plasmatic cholinesterase activity was investigated. Furthermore, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This may be directly related to MAL-induced depressive and Parkinsonian-like behaviors (Saeedi Saravi et al 2016;Mohammadzadeh et al 2018). Moreover, MAL toxicity can cause muscle weakness and easy fatigability, which are associated with damage to the nervous system and the brain (Karami-Mohajeri et al 2014;Rezg et al 2015).…”
Section: Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…This may be directly related to MAL-induced depressive and Parkinsonian-like behaviors (Saeedi Saravi et al 2016;Mohammadzadeh et al 2018). Moreover, MAL toxicity can cause muscle weakness and easy fatigability, which are associated with damage to the nervous system and the brain (Karami-Mohajeri et al 2014;Rezg et al 2015).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Mohammadzadeh and his colleagues found that crocin, saffron active components, exhibited protective effects against MAL-induced Parkinson-like behavior through reducing lipid peroxidation, improving motor deficits and anti-inflammatory effects (Mohammadzadeh et al 2018). Other natural products that approved efficacy include aged garlic extract (Ramadan et al 2017), grape seed extract (Abdel-Salam et al 2018), Aloe vera (Gupta et al 2019), caffeic acid (Rezg et al 2015), thymoquinone (Abdel-Daim et al 2020), and curcumin (Alp et al 2012). Recommendations for increasing the use of these antioxidants on a daily basis, especially those working in pesticides' factories or agriculture, may be warranted.…”
Section: Novel Treatments For Mal Poisoningmentioning
confidence: 99%
“…Recent in vivo studies mainly focused on neurodegenerative disease (e.g. Alzeimer's), obesity and diabetes, skin cancer, and liver and kidney damage (Table ).…”
Section: Mechanism Of Action Of Hydroxycinnamic Acids: Recent Advancesmentioning
confidence: 99%
“…[118][119][120] Recent in vivo studies mainly focused on neurodegenerative disease (e.g. Alzeimer's), [121][122][123][124][125][126][127] obesity and diabetes, [128][129][130] skin cancer, [131][132][133] and liver 134 and kidney damage 135 (Table 4).…”
Section: Caffeic Acid: Recent Advancesmentioning
confidence: 99%
“…Recently, various functions have been identified for caffeic acid and its derivatives, including anti-tumour [7], anti-inflammatory [8], and antioxidation [9] effects and as a prophylactic for malathion-induced neuropeptides [10]. In addition, many caffeic acid analogues also had great potential as anti-fungal and anti-bacterial agents [11].…”
Section: Introductionmentioning
confidence: 99%